Nutrient management and irrigation scheduling effect on blackgram (Vigna mungo) - frenchbean (Phaseolus vulgaris) yield, economics, water productivity and soil properties - SINGH, Y. P.; TOMAR, SANDEEP S.; SINGH, ANIL KUMAR; YADAV, R. P. (Journal of Soil and Water Conservation, 2018)
A field experiment was conducted at Morena centre during two consecutive years to study the effect of levels of recommended doses of nutrients (RDN) and irrigation scheduling on growth, yield, economics, quality, water productivity and soil properties for black gram (Vigna mungo L.) and French bean (Phaseolus vulgaris L.) grown in sequence. The results revealed that additions of 15 N: 45 P2O5: 15 K2O: 22.5 S kg ha-1 (75% RDN) + 2.5 t FYM ha-1 in black gram and 75 N: 45 P2O5: 30 K2O: 22.5 S kg ha-1 (75% RDN) + 2.5 t FYM ha-1 in French bean achieved maximum growth, yield attributes and seed yield by 23.6% and 26.8% compared with 100% RDN, respectively. Likewise, irrigation at 0.6 IW/CPE ratio (4,079 m-3 water ha-1) was significantly higher growth, yield attributing characters and seed yield of french bean by 36.1% compared with 0.4 IW/CPE ratio (2,741 m-3 water ha-1). The protein yield, net returns and B:C ratio of black gram and French bean were also observed higher under application of 75% RDN + 2.5 t FYM ha-1 with irrigation in French bean at 0.6 IW/CPE ratio. Similarly, higher water productivity of black gram and French bean were recorded under application of 75% RDN + 2.5 t FYM ha-1 when compared with control. The maximum amount of total water was used under 0.8 IW/CPE (5415 m-3 water ha-1) and minimum under 0.4 IW/ CPE, whereas reverse trend for water productivity was observed. After harvest of second crop of French bean, maximum availability of N was observed under 0.8 IW/CPE, whereas maximum availability of P, K and S was observed under 0.4 IW/CPE. The application of 75% RDN + 2.5 t FYM ha-1 revealed for higher availability of N, P, K and S in soil compared to 100% RDN. The two years experimental data indicates that addition of nutrients i.e. 75% RDN + 2.5 t FYM ha-1 in each crop and irrigation at 0.6 IW/ CPE in winter season crop produced highest seed and protein yield, economic benefits and improved soil properties of rainy season crop of black gram and winter season French bean grown in sequence.